Progression of Cardiovascular Manifestations in Adults and Children With Mucopolysaccharidoses With and Without Enzyme Replacement Therapy - Poswar, Fabiano de Oliveira; Santos, Hallana Souza; Santos, Angela Barreto Santiago; Berger, Solano Vinicius; Souza, Carolina Fischinger Moura de; Giugliani, Roberto; Baldo, Guilherme (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiovascular involvement is among the main features of MPS disorders and it is also a significant cause of morbidity and mortality. The range of manifestations includes cardiac valve disease, conduction abnormalities, left ventricular hypertrophy, and coronary artery disease. Here, we assessed the cardiovascular manifestations in a cohort of children and adults with MPS I, II, IV, and VI, as well as the impact of enzyme replacement therapy (ERT) on those manifestations. Methods: We performed a chart review of 53 children and 23 adults with different types of MPS that had performed echocardiograms from January 2000 until October 2018. Standardized Z scores were obtained for heart chamber sizes according to the body surface area. When available, echocardiographic measurements that were performed before ERT and at least 18 months after that date were used for the assessment of pre- and post-treatment parameters. Results: Left side valvular disease was a frequent finding, with mitral and aortic thickening being reported in most patients in all four MPS types. Left atrium dilatation was present in 26% of the patients; 25% had increased relative wall thickness; 28% had pulmonary hypertension. The cardiovascular involvement was, in general, more prevalent and more severe in adults than in children, including conduction disorders (40% vs 16%), mitral stenosis (26% vs 6%), aortic stenosis (13% vs 4%), and systolic dysfunction (observed in only one adult patient). ERT promoted a significant reduction of the left ventricular hypertrophy parameters, but failed to improve valve abnormalities, pulmonary hypertension, and left atrial dilatation. Conclusions: Adult patients with MPS may develop severe cardiovascular involvement, not commonly observed in children, and clinicians should be aware of the need for careful monitoring and timely management of those potentially life-threatening complications. Our results also confirm the impact of long-term ERT on left ventricular hypertrophy and its limitations in reversing other prevalent cardiovascular manifestations.